SAT0196 Impress 2 (International Multicentric Prospective Study on Pregnancy in Systemic Sclerosis). Prospective, Case-Control Study of Pregnancy in Systemic Sclerosis. (15th July 2016) - Betelli, M.; Ramoni, V.; Meroni, M.; Allanore, Y.; Baresic, M.; Beneventi, F.; Caramaschi, P.; Cutolo, M.; Favaro, M.; Govoni, M.; Hachulla, E.; Limonta, M.; et al.
Abstract : Background: Data on pregnancy in Systemic Sclerosis (SSc) are limited;we recently published IMPRESS, a retrospective multicenter study that compared 109 pregnancies from 99 SSc women with a general obstetric population (GOP).In SSc women preterm deliveries (PD, < W37: 25% vs.12%) and severe preterm deliveries (SPD, < W34: 10% vs. 5%), intrauterine growth restriction (IUGR, 6% vs. 1%) and very-low-birth-weight babies (VLBW, 5% vs. 1%) were significantly more frequent than GOP.Multivariable analysis found that corticosteroid use was associated with PD, while folic acid and anti-Scl70+ was protective.The disease remained stable in most SSc patients, but there were 4 cases of progression within 1 year from delivery Methods: This is a fully prospective, multicenter case-control study of 3 groups of people: 1) 100 pregnant SSc patients, 2) 200 not-pregnant SSc women (matched for age, auto-antibody pattern, limited/diffuse/sine scleroderma – L/D/S – form and obstetric history), 3) 200 healthy pregnant women (matched for age and obstetric history).We will prospectively investigate disease activity during pregnancy and further year, pregnancy outcome and children health status at birth and at 1 year Results: 39 pregnancies are currently ongoing, 22 patients have already delivered:8 ACA+ (6 L, 1 D, 1 S), 13 Scl70+ (7 L, 4 D, 2 S), 1 RNA-P3+ D, 2 L form without SSc-specific autoantibodies.We observed 4 miscarriages (1 ACA+, 2 Scl70+, 1 RNA-P3+), 1 therapeutic abortion at W22 (ACA+ D in treatment with prednisone 15mg/d and cyclophosphamide), 1 early voluntary termination, 2 SPD in Scl70+ L (1 cesarean section at W30, due to IUGR and fetal heart rate alteration;1 spontaneous in twin pregnancy: one twin with VLBW and both of them with respiratory distress at birth), 2 PD (both of them in SCl70+ L disease at W 36), 1 pre-eclampsia at W 37 in Scl70+ limited disease, with pulmonary embolism during post-partum. Till now, 16 mothers and 28 SSc controls had completed one year surveillance after delivery.We observed disease progression in two cases: the ACA+D patient treated with prednisone and cyclophosphamide who underwent therapeutic abortion showed a kidney function worsening till hemodyalisis;the Scl70+L patient who underwent twin pregnancy showed significant worsening in pulmonary function testing, without specific findings at chest CT. One child, born at W36 from Scl70+L mother, died at 3 months due to cardiac malformation and aesopaghus atresia;all other children showed a regular growth at 12 months pediatric evaluation Conclusions: IMPRESS 2 is still going on, and we hope to answer to important questions: 1) are complications of SSc more frequent during pregnancy? 2) Are some autoantibodies protective for prematurity? 3) Which is the impact of prematurity on children development? Disclosure of Interest: None declared